'It will get even better': preliminary findings from a trauma-focused psychotherapy effectiveness study reveal false positive patients' long-term outcome expectations after the treatment. (19th May 2017) - Kazlauskas, Evaldas; Jovarauskaite, Lina; Mazulyte, Egle; Skruibis, Paulius; Dovydaitiene, Migle; Eimontas, Jonas; Zelviene, Paulina
Abstract: Background: There is considerable evidence that outcome expectations may predict psychotherapy outcomes. However, little is known about the long-term outcome expectations following the end of the treatment. Aims: The aim of this study was to evaluate patients' long-term outcome expectations after trauma-focused post-traumatic stress disorder (PTSD) psychotherapy in a single group effectiveness study. Methods: Twenty participants with various traumatic experiences who completed the Brief Eclectic Psychotherapy for Post-Traumatic Stress Disorder (BEPP) and all the assessments were included into the study. Self-report measures were used to evaluate the therapeutic outcomes: Impact of Event Scale–Revised (IES-R), Clinical Outcomes in Routine Evaluation–Outcome Measure (CORE-OM) at pre-treatment, post-treatment, and 6-month follow-up. Subjective Units of Distress Scale was used to measure long-term outcome expectations at post-treatment, asking participants to measure the expected distress in 6 months following the treatment. Assessments at 6-month follow-up were used to estimate the accuracy of patients' expectations of their distress at previous post-treatment assessment. Results: Significant decline of PTSD symptoms at post-treatment with large effect sizes was observed. At post-treatment assessment participants expected significant improvement of their condition in 6 months after the treatment. However, therapeutic effects remained stable at the 6-month follow-up. Conclusion: It is concluded that the PTSD patients, even after successful trauma-focused treatment, tend to expect further significant positive changes. However, therapeutic effects were stable half a year after the psychotherapy, and patients tend to have false expectations about further improvement of their condition.